208k views
3 votes
2 ( 4x - 3 ) - 8 = 4 + 2x Giving me a headache

User Idij
by
5.3k points

1 Answer

2 votes

1 Expand.

8x-6-8=4+2x8x−6−8=4+2x

2 Simplify 8x-6-88x−6−8 to 8x-148x−14.

8x-14=4+2x8x−14=4+2x

3 Add 1414 to both sides.

8x=4+2x+148x=4+2x+14

4 Simplify 4+2x+144+2x+14 to 2x+182x+18.

8x=2x+188x=2x+18

5 Subtract 2x2x from both sides.

8x-2x=188x−2x=18

6 Simplify 8x-2x8x−2x to 6x6x.

6x=186x=18

7 Divide both sides by 66.

x=\frac{18}{6}x=

​6

​18

​​

8 Simplify \frac{18}{6}

​6

​18

​​ to 33.

x=3x=3

Done Hope this helps let me know if u have any questions thank you

User Alex Radzishevsky
by
4.8k points